PARTISIPASI MASYARAKAT DALAM PEMBANGUNAN KAMPUNG WISATA "WARNA-WARNI" JODIPAN KOTA MALANG JAWA TIMUR - Kus Indarto (DIALEKTIKA: Jurnal Ekonomi dan Ilmu Sosial, 2017)
The aims of this research are to describe and analyze the Jodipan"Colorful" Village Tour community participation in the development/painting their village. Development Jodipan "Warna-Warni" Tour Village was initiated by University of Muhammadiyah Malang (UMM) students who were carrying out practical tasks. In order to do the painting, students work together with PT. Indana Paint. This research is a qualitative with descriptive method. Data were analyzed using data analysis interactive model proposed by Miles, Huberman and Saldana. The findings in the field shows that the people in Jodipan "Warna-Warni" Tour Village participate in decision-making, implementation, benefit and evaluation. Forms of community participation in the development of Jodipan "Warna-Warni" Tour Village namely: ideas participation, force participation, the participation of property, participation skill and finesse, and social participation. The degree of community participation Jodipan "Warna-Warni" Tour Village are in degrees sign ofparticipation, and are on the fifth rung, namely placation.